SYSTEMATIC LITERATURE REVIEW: IMPLEMENTATION OF KNOWLEDGE MANAGEMENT IN THE ORGANIZATION - Azizah Nurfauziah Yusril; Evy Nurmiati (LPPM Nusa Mandiri, 2021)
Knowledge management is an activity that organizations use to achieve goals and gain competitive advantages. This study features a systematic literature review that discusses the implementation of knowledge management in organizations covering 39 articles published from 2015 to 2020. This study aims to answer four research questions. The results show that the trend of knowledge management research in Indonesia is dominated by research related to the designing of knowledge management systems. The application of knowledge management in Indonesia has been applied in various fields. There are various models and methods that can be used in creating a knowledge management system